Hubungan Self Efficacy dengan Stres Akademik pada Siswa SMP Negeri 10 Padang - Zaimi, Mawarda; Zikra, Zikra (Lembaga Yasin AlSys, 2025)
This research aims to determine the relationship between self-efficacy and academic stress in students at SMP N 10 Padang. This research is motivated by the behavior of students who show symptoms of academic stress such as not focusing on studying, often feeling anxious when facing unfinished learning problems and the pressure they feel while studying. This research aims to reveal the phenomenon of self-efficacy and academic stress and describe the picture that occurs and determine the relationship between self-efficacy and academic stress. This research uses quantitative methods through a correlational descriptive approach. The sample for this research was 256 students using Stratified Random Sampling techniques. Obtaining data in this research uses the Pearson Product Moment correlation formula. The results of the research show that (1) the self-efficacy of students at SMP N 10 Padang is in the medium category with an average score of 84.33 (67.3%), (2) the students' academic stress is in the medium category with an average score of 79 .64 (60.54%) and (3) there is a significant negative relationship between self-efficacy and academic stress in students at SMP N 10 Padang with a correlation of -0.608. This means that the higher the self-efficacy, the lower the student's academic stress, and vice versa. Based on the research results, teachers are asked to play an active role in efforts to increase students' self-efficacy and reduce students' academic stress by providing service assistance and counseling to students. The services provided include information services, individual counseling services, group guidance services and group counseling services.